The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1055/s-0042-1750122
|View full text |Cite
|
Sign up to set email alerts
|

Video-Based Microsurgical Education versus Stationary Basic Microsurgical Course: A Noninferiority Randomized Controlled Study

Abstract: Background Repetitive training is essential for microsurgical performance. This study aimed to compare the improvement in basic microsurgical skills using two learning methods: stationary microsurgical course with tutor supervision and self-learning based on digital instructional materials. We hypothesized that video-based training provides noninferior improvement in basic microsurgical skills. Methods In this prospective study, 80 participants with no prior microsurgical experience were randomly div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…23 Published models include the use of bead transfer, latex glove, and synthetic tubing (e.g., polytetrafluoroethylene, GorTex, and silastic tubing) to simulate vessels and peripheral nerves. [15][16][17][18][19][20][21][22]26,28,32,[34][35][36]45,51,52 These are effective models in skill development and retention demonstrating construct and content validity with the addition of synthetic-based models having face validity. 24 These models do not depend on use of live or cadaveric tissue and are cost-effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Published models include the use of bead transfer, latex glove, and synthetic tubing (e.g., polytetrafluoroethylene, GorTex, and silastic tubing) to simulate vessels and peripheral nerves. [15][16][17][18][19][20][21][22]26,28,32,[34][35][36]45,51,52 These are effective models in skill development and retention demonstrating construct and content validity with the addition of synthetic-based models having face validity. 24 These models do not depend on use of live or cadaveric tissue and are cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…These models can be isolated tasks or incorporated into training curricula using cadaveric models for anastomosis practice. 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 Recent developments in microsurgical simulation and education even eliminate the use of a standard operating room microscope and instead incorporate a portable binocular microscope or monocular smartphone technology with video recording and feedback. 35 36 37 Some curricula rely on progression of skills based on learner postgraduate year (PGY), but reported outcomes are often not related to PGY level.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Currently, developing microsurgery skills seems to be an inherent part of surgical specialization. Studies showed that learning microsurgery on the basic level may be achieved by self-learning, using solely tutorial videos as a guide [99]. This creates a great possibility, especially for young doctors, and contribute to the more common availability of microsurgery procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Current microsurgical simulation and curricula predominantly [3,4,15] evaluate one aspect; technical performance, including assessment with lower fidelity models on synthetic and ex-vivo tissue, tracking and showing progression with objective assessment tools [16,17]. One study [18] perfused an ex-vivo chicken model with "blue blood" with ICG and experts assessed the patency of the vessel, this provides a high-fidelity model without the use of live animal.…”
Section: Accepted Manuscriptmentioning
confidence: 99%